Following the leader ruling China, from Deng Xiaoping to Xi Jinping - Lampton, David M. (Berkeley University of California Press, 2014)
With unique access to Chinese leaders at all levels of the party and government, best-selling author David M. Lampton tells the story of China?s political elites from their own perspectives. Based on over five hundred interviews, Following the Leader offers a rare glimpse into how the attitudes and ideas of those at the top have evolved over the past four decades. Here China?s rulers explain their strategies and ideas for moving the nation forward, share their reflections on matters of leadership and policy, and discuss the challenges that keep them awake at night.
Includes bibliographical references and index.
Keywords: Political leadership--China.